The Influence of Guidance and Counseling on the Learning Achievement of High School Students With Disabilities - Ida Septiani Sari; Nilam Irma Damayanti (JAMBURA Guidance and Counseling Journal, 2022)
The achievement of deaf students can be achieved from the ability of the students themselves and the most important thing is the guidance from competent supervisors. The purpose of this study was to determine the effect of guidance and counseling on the achievement of deaf high school students. The research method uses a qualitative analytical approach. Collecting data using the interview method. The results of the study concluded (1) the characteristics of deaf students; (2) the learning program carried out; (3) learning methods for deaf students; (4) students' abilities; (5) achievements that have been achieved.